دراسة النشاطية البيولوجية ومضادات الأكسدة للبرطلاق النامي في ترب مختلفة - بن خليفه, أنفال مختاري, شيماء عازب عثمان, بسمه غريسى, سارة (University of Eloued جامعة الوادي, 2023)
This work aims to study the biological and antioxidant activity and quantitative determination of the polyphenols and flavonoids of the methanolic extract of the plant Portulacae oleracea L. , Growing in different soils . This study was based on the comparison between the three places according to their soil type in which the area of Lizerg (L) is charcterised by a sandy soil , the area of Bildet Amor (BA) has clay soil, and Tebesbest ( T) has sandy clay soil. The results of estimation of ash and organic matter content manifested that There is a discrepancy between the different regions , indicating that the Lizerg (L) region had a higher percentage of 35.05% in ash content , whereas Tebesbest (T) was the best in organic matter with a percentage of 35.70%. The Singleteon and Rossi method was applied for the quantitative determination of polyphenols , where the Tebesbest (T) area showed the highest percentage of polyphenols estimated 74.38 mg ЄAG /g Ex , compared with the two areas, area of Bildet Amor and Lizerg , estimated at 61.11and 33.67 respectively, Whereas, Alcl3 was applied to estimate the flavonoids, where the Lizerg region contained the highest amount of flavonoids estimated at 26.22 . The results of the anti-oxidation activity of free radical DPPH● showed that the area of Lizerg (L) exceeded the inhibitory capacity of IC50 = 4.08 ± 0.03 μg/ml. Whereas the results of the anti-oxidant activity of the FRAP test showed that the FRAP region was superior to the Lizerg (L) region EC50=0.66 μg/ml over the remaining areas, as for the Hémolyse test, the results showed the distinction of the area of Bildet Amor (BA), which recorded the lowest concentration in the rate of Hémolyse, estimated at 11.83%.concentration 1mg/ml .As a result , the experiments have proven that these differences are due to several factors , most notably soil quality, water quality and the physiological state of the plant, and from here conclude that soil has an effect on the chemical properties of the plant, and this is through the observed differences between the three regions in the quantitative content of polyphenols and flavonoids in addition to the tests .
تنوع حيوي و فيزيولوجيا النبات
Keywords: نبات البرطالق; Portulacae oleracea L